A Video For Teaching English Tenses - Unsiah, Frida; Danayanti Degeng, Putu Dian; Kusumawardani, Irene Nany (LPPM Universitas Mercu Buana Yogyakarta, 2016)
AbstractStudents of English Language Education Program in Faculty of Cultural Studies Universitas Brawijaya ideally master Grammar before taking the degree of Sarjana Pendidikan. However, the fact shows that they are still weak in Grammar especially tenses. Therefore, the researchers initiate to develop a video as a media to teach tenses. Objectively, by using video, students get better understanding on tenses so that they can communicate using English accurately and contextually. To develop the video, the researchers used ADDIE model (Analysis, Design, Development, Implementation, Evaluation). First, the researchers analyzed the students’ learning need to determine the product that would be developed, in this case was a movie about English tenses. Then, the researchers developed a video as the product. The product then was validated by media expert who validated attractiveness, typography, audio, image, and usefulness and content expert and validated by a content expert who validated the language aspects and tenses of English used by the actors in the video dealing with the grammar content, pronunciation, and fluency performed by the actors. The result of validation shows that the video developed was considered good. Theoretically, it is appropriate to be used English Grammar classes. However, the media expert suggests that it still needs some improvement for the next development especially dealing with the synchronization between lips movement and sound on the scenes while the content expert suggests that the Grammar content of the video should focus on one tense only to provide more detailed concept of the tense.